Menghidupi Cinta Tanpa Syarat: Konsep 'Caritas' dalam Ajaran Katolik dan Dampaknya bagi Masyarakat Plural - Rikha Emyya Gurusinga; Regina Dipa Gurusinga; Armenda Barus (Sekolah Tinggi Katolik Touye Paapaa Deiyai, 2025)
This study aims to analyze the theological concept of caritas in Catholic Church teachings and evaluate its impact on shaping interfaith relations and social action in a pluralistic society. The approach used is qualitative-reflective with a literature study method on Church documents, the Holy Scriptures, and pastoral and social theology literature. The author also examines the practical implementation of the Catholic Church's charitable works in Indonesia, which involve interfaith cooperation. The results of the study show that caritas, as unconditional love, is not only a teaching of faith but also an ethical foundation that encourages the Church to build dialogue, cooperation, and social solidarity amid diversity. These findings confirm that the value of caritas can serve as a bridge between religions and strengthen the Church's witness as an inclusive community of love. The article concludes with a suggestion that the Church's pastoral approach should place greater emphasis on fostering the value of caritas as the basis for social transformation and peace.